Soccer players efficacy belief, CSAI-2C, SCAT perception and success comparison - Barış Ozer; Serdar Kocaeksı (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to compare to relationships anxiety, efficacy beliefs and perception of success that are playing football at 11-13. Youth and Sports Club Soccer Branch of Anadolu University U-13 players were participated in this study. Measurements were applied to athletes two times selection of Anadolu University. Competition State Anxiety Inventory - Child Version-2 (CSAI-2C), Competition Trait Anxiety Inventory-Child Form (SCAT-C), Self-Efficacy (SES), Perception of Success - Children's Version (POSQ-CH) is used to collection data. Descriptive statistics and Pearson Moment Correlation analysis were used to calculate data. Between the first and second measurement after the analysis, SCAT-C and a positive correlation between somatic anxiety (r =.465, p lt;0.01), Scat Self-Efficacy with negative (r = -.455, p lt;0.01), Cognitive SCAT and a positive correlation between anxiety (r =.706, p lt;0.01), Scat and a positive correlation between somatic anxiety (r =.722, p lt;0.01), there was a negative correlation among self-efficacy and SCAT. As a result, there were some significant relationships between competitive state anxiety and state competitive with goal settings